Optimizing Fashion Retail Shelf Management for Enhanced Consumer Experience: A Literature Review - Maria Loura Christhia (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
This study aims to optimize shelf display management in the fashion retail industry to cater to the evolving needs and desires of consumers for specific products. With the ever-expanding range of fashion items available in retail stores, the limited space on display shelves poses a significant challenge. Additionally, trendy, and high-demand fashion products often experience quick sell-outs, necessitating frequent restocking. Effective management of shelf displays is pivotal in enhancing consumer satisfaction and stimulating impulse purchases by maximizing product visibility and exposure. In the realm of fashion retail, shelf display management can be broadly categorized into macro and micro levels, encompassing strategic overall layout and precise product allocation within specific fashion categories. However, these approaches heavily rely on the availability of demand and transaction data, which can be challenging for small and medium-sized fashion enterprises with limited data resources. This literature review underscores the research opportunities for optimizing shelf display management, particularly in the context of fashion retail businesses facing data limitations. It recognizes that through thoughtful facility layout design, coupled with suitable adjustments and modifications, the challenges associated with shelf displays in fashion retail stores can be effectively addressed.